Heterogenous Switching Costs - Gary Biglaiser; Jacques Crémer; Gergely Dobos (Center for Economic Studies and ifo Institute (CESifo), 2014)
We consider a simple two period model where consumers have different switching costs. Before the market opens, there was an incumbent who sold to all consumers. We identify the equilibrium both with Stackelberg and Bertrand competition and show how the presence of low switching cost consumers benefits the incumbent, despite the fact that it never sells to any of them.
Keywords: D43; L13; 330; switching cost